2016
DOI: 10.25011/cim.v39i6.27495
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes in the Cerebrum, Cerebellum and Corpus Callosum in Migraine Patients

Abstract: Purpose: The purpose of this study was to demonstrate the relationship among the cerebrum, cerebellum and corpus callosum in migraine patients. Methods: This work was conducted with cooperation of the Turgut Özal Medical Faculty, Department of Anatomy and Neurology. Migraine patients were divided into four groups: new patients; 1-5 years; 5-10 years; and, more than 10 years. All patients (n=75) and control subjects (n=20) underwent Magnetic Resonance Imaging (MRI) and brain images were processed by ONIS and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…A number of neuroimaging studies have shown structural and functional alterations in cerebellar regions in migraineurs and increased connectivity during nociception between the cerebellum and brainstem regions and between the cerebellum and thalamic regions . In this study, we found that structural co‐variance patterns between the right hippocampus and the right cerebellar white matter were strengthened in migraineurs.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…A number of neuroimaging studies have shown structural and functional alterations in cerebellar regions in migraineurs and increased connectivity during nociception between the cerebellum and brainstem regions and between the cerebellum and thalamic regions . In this study, we found that structural co‐variance patterns between the right hippocampus and the right cerebellar white matter were strengthened in migraineurs.…”
Section: Discussionsupporting
confidence: 57%
“…42 Additionally, in pediatric patients with complex regional pain syndrome, those patients with higher levels of pain-related fear had stronger functional connectivity between the left amygdala and the right hippocampus. 43 Strengthening of Hippocampal-Cerebellar Co-Variance Patterns in Migraine.-A number of neuroimaging studies have shown structural and functional alterations in cerebellar regions in migraineurs [44][45][46] and increased connectivity during nociception between the cerebellum and brainstem regions and between the cerebellum and thalamic regions. 46 In this study, we found that structural co-variance patterns between the right hippocampus and the right cerebellar white matter were strengthened in migraineurs.…”
Section: Discussionmentioning
confidence: 99%
“…Given the downstream association of the cerebellum with inputs from the TGVS and somatosensory cortex, the delayed but higher (13 mM) sodium impacts observed may reflect nociceptive and potential vestibular impacts of migraine in this acute model. A number of studies hint at cerebellar dysfunction in migraine: gray and white matter abnormalities [15,36], cerebral function tests to assess spatiotemporal and motion processing [30,33,34,39], ASL perfusion effects [29,56] and a recent fMRI study [35] tracing connectivity between the cerebellum and rostral pons, thalamus and aqueduct have demonstrated differences in the cerebella of chronic migraineurs in the interictal state and with the onset of nociceptive pain. Moulton and coworkers [38] demonstrated BOLD activation in multiple cerebellar areas as a response to aversive sensory input and nociceptive stimulus processing.…”
Section: Discussionmentioning
confidence: 99%
“…Structural corpus callosum abnormalities such as corpus callosum atrophy (36) and white matter axonal loss (37) have been shown in migraine patients, also correlating with disturbances of the anterior cingulate cortex, which is involved in pain processing (38). However, since PMBS was normal in interictal migraine, we found no evidence of any permanent deficit.…”
Section: Discussionmentioning
confidence: 99%